Pediatric Acute Kidney Injury: Focusing on Diagnosis and Management - Myung Hyun Cho (Korean Society of Pediatric Nephrology, 2020)
Acute kidney injury (AKI) is common in critically ill children, and is associated with increased mortality and long-term renal sequelae. The definition of pediatric AKI was standardized based on elevation in serum creatinine levels or decrease in urine output; accordingly, epidemiological studies have ensued. Although new biomarkers appear to detect AKI earlier and predict prognosis more accurately than traditional markers, they are not frequently used in clinical setting. There is no validated pharmacological intervention for AKI, so prevention and early detection are the mainstays of treatment. For high risk or early stage AKI patients, optimization of volume status and blood pressure, avoidance of nephrotoxins, and sufficient nutritional support are necessary, and have been demonstrated to be effective in preventing the occurrence of AKI and improving prognosis. Nevertheless, renal replacement therapy is needed when conservative care fails.